(untitled) (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2021)
Menopause is a normal physiologic process, defined as the permanent cessation of menses for 12 months or more due to cessation of ovarian hormone production. The age at natural menopause is between 45 years and 50 years. Early menopause is defined as menopause occurring before the age of 45 years, while premature menopause occurs before the age of 40 years. Around 20% of the patients suffer from severe menopausal symptoms, 60% suffer from mild symptoms and 20% may have no symptoms at all. Health workers are searching for different ways to manage menopause to minimize discomfort and inconvenience during menopausal transition, so as to improve the quality of life of these women. The aim of the study was to study the impact of menopausal symptoms on quality of life using MRS scale, HFRDIS scale, WHO-BRFE scale. In Western India very few studies have been done on menopause and no published literature has been found among these females. Thus, the present study focuses on the various climacteric symptoms on quality of life using the Greene climacteric scale and Menopause Specific Quality Of Life Scale among females of Pune Maharashtra.